Faktor Risiko Kejadian Demam Berdarah Dengue pada Anak Usia 5-14 Tahun di Kota Semarang - Ambar Atikah Zain; Widya Hary Cahyati (Poltekkes Kemenkes Padang, 2022)
DHF cases in Semarang City from 2020 to June in the 5-9 year age group were 59 cases, in the 10-14 year age group 66 cases were the highest cases among other ages. The purpose of this study was to determine the risk factors for the incidence of DHF in children aged 5-14 years in the city of Semarang. This type of research is a quantitative research, analytical observational case control study design. The research sample was 70 cases and 70 controls. Sampling technique with cluster sampling. The results of the study concluded that the use of used goods was in the bad category with the highest percentage of 74.3%, the presence of stagnant water sources in/near the house as much as 67.1%, and the behavior of closing water reservoirs was bad, which was 65%. There is a relationship between inundated water sources at/near the house (p-value=<0.000; OR=6.355; 95% CI:2.806-14,384); behavior of draining water reservoirs (p-value=<0.002; OR=3,088; 95% CI:1.474-6.469); and not closing water reservoirs (p-value=<0.008; OR=2.625; 95% CI:1,277-5,398). Gender (p=0,865; OR=1,059; 95% CI=0,014-2,058), the use of used goods (p=0,699; OR=1,161; 95% CI=0,544-2,481) is not a risk factor for DHF. It is recommended that the community always carry out activities to eradicate mosquito nests inside and outside the home so that it is not used as a breeding ground for mosquitoes.